Case report: A non-obstructive azoospermia patient with heat shock factor-2 mutation. Issue 31 (31st July 2020) - Zhao, Haiyue; Zhang, Hongguo; Xi, Qi; Li, Leilei; Zhu, Haibo; Hu, Xiaonan; Liu, Ruizhi
Abstract: Rationale: Infertility is a common medical condition that affects nearly 15% of the world population. Non-obstructive azoospermia (NOA) is one of the most severe forms of male infertility. Some common structural variants, single nucleotide polymorphisms (SNPs), and genetic factors were reported to be associated with NOA. However, the underlying etiology and genetic mechanism(s) remain largely unclear. This report aimed to describe the associated mutation of the heat shock factor-2 (HSF2) gene in Chinese infertile men with NOA. Patient concerns: An apparently healthy 27-year-old man with a body mass index (BMI) of 23.31 kg/m 2 had a 2-year history of primary infertility. Diagnoses: The semen analysis of the patient showed a sperm concentration of 0/mL in 6.5 mL of semen. The patient was diagnosed with NOA by performing the comprehensive examinations including a detailed medical history, physical examination, chromosome analysis, Y-chromosome microdeletions, semen analysis, and hormone profiles. Interventions: The couple received artificial insemination by donor (AID) and a healthy girl was born after the embryo transfer. Outcomes: We found a novel deletion-insertion variation c.326_326delinsGGAAGGTGAGCTATTGT in the exon 3 of the HSF2 gene by performing next-generation sequencing on him who was diagnosed NOA. We performed Sanger sequencing on this patient and confirmed the heterozygous missing insertion mutation in the patient. This is a novel mutation. The variant was heterozygous and categorized as pathogenic. Lessons: A novel deletion-insertion variation c.326_326delinsGGAAGGTGAGCTATTGT in the exon 3 of HSF2 gene HSF2 is predicted to be pathogenic and associated with the occurrence of NOA.